Metal 3D Printed Nickel‐Based Self‐Catalytic Reactor for COx Methanation. Issue 12 (14th April 2022) - Wang, Chengwei; Peng, Xiaobo; He, Yingluo; Fan, Jiaqi; Lin, Xingyi; Jiang, Lilong; Tsubaki, Noritatsu
Abstract: 3D printing technology can rapidly transform digital model into physical realization, and has been widely studied in many fields. However, its developments are very slow in the fields of catalysis and reaction engineering, due to harsh application environments. Here, we report that metal 3D printing is used to prepare Nickel‐based Self‐Catalytic Reactor (Ni‐SCR) for COx methanation. The optimized Ni‐SCR samples exhibit unique surface properties. The catalytic results reveal that they also possess premium methanation performance. This work will facilitate the developments both in 3D printing technologies and novel catalytic systems. Abstract : The Nickel‐based self‐catalytic reactor (Ni‐SCR), which was prepared by metal 3D printing technology, provides an innovative method that couples catalyst with reactor. The optimized Ni‐SCR via calcination or acid leaching (denoted as Ni‐SCR‐Calcined and Ni‐SCR‐Acid) was performed for COx methanation. The catalytic performance unveiled that Ni‐SCR‐Calcined/Acid displayed premium COx conversion and methane selectivity.